Intermediate Islamic Finance - Nabil Maghrebi ; Abbas Mirakhor and Zamir Iqbal (Singapore John Wiley, 2016)
"Explore Islamic finance at a deeper level Intermediate Islamic Finance: Theory and Practice fills the gap for students and professionals who are already familiar with the fundamentals of Islamic finance, but would like to gain an enhanced understanding of Islamic finance theories and practices. This comprehensive text provides you with coverage of global developments and describes the role of Islamic finance within
Include Reference and Index
Keywords: Islamic countries -- Finance -- Finance--Religious aspects--Islam